Management Public Relations Dompet Dhuafa - Yudhi Fahruddin (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2021)
Amil Zakat Institution Dompet Dhuafa is one of the zakat institutions owned by the Indonesian people which is not only engaged in Zakat, Infaq, Alms and Waqf (ZISWAF), but is engaged in the humanitarian sector which includes, poverty, education and social. To support the activities carried out by LAZ Dompet Dhuafa cannot be separated from communication and information, in carrying out good communication it requires a means called media. This study aims to determine (1) the method of identifying Public Relations problems at LAZ Dompet Dhuafa; (2) the process of planning and program of LAZ Dompet Dhuafa; (3) LAZ Dompet Dhuafa's communication and action strategy; and (4) the process of evaluating the LAZ Dompet Dhuafa program. This study uses a qualitative method with a single case holistic exploratory case study approach. The results showed that LAZ Dompet Dhuafa did not conduct special research related to program planning; research is carried out only through new facts in the field through pre-existing programs. LAZ Dompet Dhuafa's thematic and non-thematic program planning is carried out through annual work meetings, while the main messages to be conveyed to external parties are conveyed through the official website and social media. The program evaluation carried out did not involve the external public.